THE ROLE OF TEACHERS AS VALUE, EMPATHY, AND CHARACTER BUILDERS IN THE ERA OF SOCIETY 5.0: A LITERATURE REVIEW ON CHALLENGES AND STRATEGIES FOR INTEGRATING HUMANITARIAN VALUES IN DIGITAL EDUCATION - Opi Irawansah; Mohammad Ahmad Bani Amer; Khuloud Mustafa Alouzi (Adisam Publisher, 2025)
Digital transformation in the era of Society 5.0 has brought fundamental changes in the world of education, demanding the role of teachers not only as conveyors of knowledge, but also as builders of values, empathy, and character of students. The integration of advanced technologies such as artificial intelligence, Internet of Things, and big data in the learning process presents new challenges, especially in maintaining and instilling human values amidst the swift flow of digital information. Teachers are faced with the need to balance the use of technology with the cultivation of moral values, empathy and character, so that students are not only intellectually capable, but also emotionally and socially mature. This research uses a literature study method with a qualitative approach to examine the role of teachers, the challenges faced, and strategies for integrating human values in digital education. The results show that strengthening humanist digital literacy, integrating digital ethics education in the curriculum, and collaboration between schools, families and communities are the main strategies in building a generation with strong character and high empathy in the era of Society 5.0.